2007
DOI: 10.1080/15017410600973234
|View full text |Cite
|
Sign up to set email alerts
|

Greek Employers’ Attitudes to Employing People with Disabilities: Effects of the Type of Disability

Abstract: The aim of this cross-sectional study was to answer two central research questions:(i) what are Greek employers' attitudes to employing people with a range of disabilities; and (ii) do employers' attitudes differ according to the type of disability? The study sample comprised 102 local employers with small-sized retail trade and service businesses located in semi-urban areas of Lesvos and Chios, Greek islands in the North Aegean Sea. The results show that employers' attitudes differed depending on the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
(20 reference statements)
1
25
0
1
Order By: Relevance
“…More specifically, a body of research examines workplaces and employees with schizophrenia. Zissi et al (2007) surveyed 102 local employers in small-sized retail and trade businesses in the Greek Islands. They found only 28% and 34% of employers respectively indicated a willingness to hire workers with schizophrenia and depression.…”
Section: Mental Health Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, a body of research examines workplaces and employees with schizophrenia. Zissi et al (2007) surveyed 102 local employers in small-sized retail and trade businesses in the Greek Islands. They found only 28% and 34% of employers respectively indicated a willingness to hire workers with schizophrenia and depression.…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…According to Scheid (2005), 'one of the most critical barriers to the employment of individuals with mental disabilities (sic) is the degree of social stigma such disabilities incur' (p. 670). This accounts for one reason why workers cannot find or retain employment (Krupa et al 2009;Schulze and Angermeyer 2003;Zissi et al 2007). In particular, stigma associated with schizophrenia is one of the most common barriers to employment (Schulze and Angermeyer 2003;Zissi et al 2007).…”
Section: Mental Health Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that employers would like prospective employees to disclose a mental health problem at the application stage (80% in 2006, n = 550, 77% in 2009, n = 500) (Little et al 2010). diabetes, back injury) or a candidate with no disability (Glozier, 1998;Koser et al 1999;Bricout & Bentley, 2000;Hazer & Bedell, 2000;Gouvier et al 2003;Pearson et al 2003;Reilly et al 2006;Zissi et al 2007). diabetes, back injury) or a candidate with no disability (Glozier, 1998;Koser et al 1999;Bricout & Bentley, 2000;Hazer & Bedell, 2000;Gouvier et al 2003;Pearson et al 2003;Reilly et al 2006;Zissi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most, however, had never employed a person with a mental illness, and as a group expressed a moderate to high degree of concern regarding the potential applicant's work personality and social skills, particularly the possibility that they may be unable to interact appropriately with workmates, or that they may become violent [37 ]. A survey of Greek employers' attitudes to employing people with disabilities [38 ] showed that people with mental disabilities (such as schizophrenia or depression) were considered to have almost no chance of securing competitive employment. A common belief, that there are no effective treatments, may also keep employers from addressing workplace mental health problems [8].…”
Section: Barriers To Effective Mental Disability Managementmentioning
confidence: 99%